Plant Natural Products for Human Health - Zhang, Hongjie (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Plants have served mankind as an important source of foods and medicines. While we all consume plants and their products for nutritional support, a majority of the world population also rely on botanical remedies to meet their health needs, either as their own "traditional medicine" or as "complementary and alternative medicine". From a pharmaceutical point of view, many compounds obtained from plant sources have long been known to possess bio/pharmacological activities, and historically, plants have yielded many important drugs for human use, from morphine discovered in the early nineteenth century to the more recent paclitaxel and artemisinin. Today, we are witnessing a global resurgence in interest and use of plant-based therapies and botanical products, and natural products remain an important and viable source of lead compounds in many drug discovery programs.This Special Issue on "Plant Natural Products for Human Health" compiles a series of scientific reports to demonstrate the medicinal potentials of plant natural products. It covers a range of disease targets, such as diabetes, inflammation, cancer, neurological disease, cardiovascular disease, liver damage, bacterial, and fungus infection and malarial. These papers provide important insights into the current state of research on drug discovery and new techniques. It is hoped that this Special Issue will serve as a timely reference for researchers and scholars who are interested in the discovery of potentially useful molecules from plant sources for health-related applications.